Micronutrients Intake and Mathematics Achievement among Primary School Children in Magelang, Central Java - Arika, Romiza; Anantanyu, Sapja; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Micronutrient deficiency in school children is estimated at more than 2 million children. Deficiency of micronutrients causes damage to the physical functioning of children, impaired cognitive function, learning processes that are less than optimal, and poor academic performance. This study aimed to analyze the relationships between iodine, iron, zinc intake, and math achievement primary school children. Subjects and Method: This was an obser